India’s Support for Palestine and India’s Stand on Palestine Policy by Modi: India's Solidarity and Support in the Palestinian Struggle (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India's solidarity with the Palestinian people and its mentality to the Palestinian inquiry was given voice amid our freedom struggle by Mahatma Gandhi. From that point forward, compassion with the Palestinian reason and companionship with the people of Palestine have turned into an essential piece of India's foreign policy. India was the first Non-Arab State to perceive PLO as sole and authentic delegate of the Palestinian people in 1974. India was one of the main nations to perceive the State of Palestine in 1988. In 1996, India opened its Representative Office to the Palestine Authority in Gaza, which later was moved to Ramallah in 2003. India's historic and principled help to the Palestinian people amid the freedom struggle proceeded even after autonomy. Furthermore, Nehru's supposition of power as the primary Prime Minister of the nation added congruity to its post-independent Palestine policy. In this Article, we studied about the India’s support in Palestine problem and India’s stand on Palestine Policy by Modi.